Differential Interspecific Adaptation to Abiotic Stress by Plantago Species - Teixeira, António; Toorop, Peter E.; Iannetta, Pietro P. M. (Frontiers in Plant Science, 2020)
The success of seed-based conservation and restoration efforts using native plant species is largely determined by ensuring two key life-history transitions are accommodated. These are: from ‘seed to seedling’, and ‘seedling to established plant’. In turn, optimisation of these life-history transitions are determined by a ‘genetic x environmental’ interaction, and latter largely characterised by localised climatic (abiotic) conditions. It is these environmental- or abiotic stress-factors that can act as natural selection agents for specific plant-trait combinations, or phenotypes. In turn, such adaptation may also limit a species range. To test the relationship between these two early plant life history stages transitions, ‘seed to germinated seed’ and ‘germinated seed to established seedling’, the attributes were characterised for two species of Plantago that occupy contrasting environments - and since these species have potential for native seed-based habit restoration and conservation. The species were: P. coronopus (L.), localised at higher, cooler and wetter altitudes, and P. lanceolata (L.), characterised as occupying lower, warmer and drier altitudinal clines. Seeds were collected from ten accessions of six natural populations spanning four European countries for both P. lanceolata and P. coronopus. Seed germination (G) and seedling establishment (S) data were determined at six temperatures (T) and six water potentials (Ψ) and the data obtained was analysed using a Generalised Linear Model (GLM). The results indicate that P. coronopus has adapted physiologically to its high-altitude conditions such that seed germination and seedling establishment may be more readily achieved in this cooler environment where water is less limiting. In contrast, the lower θT of P. lanceolata better facilitates more efficient seed germination and seedling establishment in drier and warmer clines of lower altitude. In addition to establishing a genotypic (species) underpin for seed and seedling trait-differences observed, the insights gained may also be exploited to best deploy each species in situ for seed-based conservation and restoration efforts.